Jaw osteosarcoma and pregnancy: a rare coexistence - Santos, Thaís Aguiar; Américo, Márcia Gimenes; Priante, Antonio Vitor Martins; Oliveira, Maria Fernanda de; Anbinder, Ana Lia (Autopsy and Case Reports, 2022)
Osteosarcoma of the jaw represents less than 1% of all head and neck malignancies. This malignancy in pregnant women occurs in one per 1000 deliveries. We report a case of a 29-year-old woman, in the 33rd week of gestation, who presented with an expansive tumor destroying the maxillary alveolar bone, histologically composed of pleomorphic, round, spindle, or epithelioid cells and osteoid/chondroid matrix. Upon final diagnosis of osteosarcoma, the lesion was excised. To the best of our knowledge, only 10 cases of jaw osteosarcoma in pregnant women have been reported to date in the English language literature. The use of ancillary examinations, malignancy diagnosis, and cancer treatment can be challenging during pregnancy. Knowledge about jaw osteosarcoma in pregnancy can increase healthcare providers’ awareness, avoid delays and misdiagnosis and potentially improve maternal and neonatal outcomes.